PENGARUH KUALITAS LAYANAN, BIAYA KULIAH, LOKASI,BAURAN PROMOSI, KUALITAS SDM TERHADAP KEUNGGULAN KOMPETITIF PTS DI KOTA PALEMBANG - Yolanda Veybitha (JURNAL KOMPETITIF, 2017)
This study aims to measure the impact of service quality, tuition, location, promotion mix, and the quality of human resources to the competitive advantage of private colleges in the city of Palembang. In this study collected primary data and secondary data. Primary data was collected using a questionnaire distributed to students in four private colleges in the city of Palembang, while secondary data gathered from the relevant literature such as journals, books and other related publications. The total sample of 392 students with stratified random sampling technique. Processing data using SPSS version 20, the results showed that the variable quality of services, tuition, location, promotion, and the quality of Human Resource significant influence simultaneously and partially to competitive advantage Colleges in Palembang. The test results according to the theory except variable tuition fees. According to the theory costleadership, put forward Porter's variable tuition fees negatively affect where the lower the price offered by the company, the higher the level of competitive advantage. But the results of this study are supported by Kotler theory which says that "a competitive advantage can be gained if companies offer more value to consumers, either through lower prices or by providing more benefits that support the pricing more. Key Words : competitif advantage